Inter-Individual Variability in Acute Toxicity of R-Pulegone and R-Menthofuran in Human Liver Slices and Their Influence on miRNA Expression Changes in Comparison to Acetaminophen - Zárybnický, Tomáš; Matoušková, Petra; Lancošová, Bibiána; Šubrt, Zdeněk; Skálová, Lenka; Boušová, Iva (International journal of molecular sciences, 2018)
Monoterpenes R-pulegone (PUL) and R-menthofuran (MF), abundant in the Lamiaceae family, are frequently used in herb and food products. Although their hepatotoxicity was shown in rodent species, information about their effects in human liver has been limited. The aim of our study was to test the effects of PUL, MF and acetaminophen (APAP, as a reference compound) on cell viability and microRNA (miRNA) expression in human precision-cut liver slices. Slices from five patients were used to follow up on the inter-individual variability. PUL was toxic in all liver samples (the half-maximal effective concentration was 4.0 µg/mg of tissue), while MF and surprisingly APAP only in two and three liver samples, respectively. PUL also changed miRNA expression more significantly than MF and APAP. The most pronounced effect was a marked decrease of miR-155-5p expression caused by PUL even in non-toxic concentrations in all five liver samples. Our results showed that PUL is much more toxic than MF and APAP in human liver and that miR-155-5p could be a good marker of PUL early hepatotoxicity. Marked inter-individual variabilities in all our results demonstrate the high probability of significant differences in the hepatotoxicity of tested compounds among people.
Keywords: Liver; Female; biologické markery; játra; individuální biologická variabilita; Biomarkers; ženské pohlaví; drug-induced liver injury; menthofuran; lékové postižení jater; lidé; Biological Variation, Individual; acetaminophen; microRNA; monoterpeny; paracetamol; Male; Cyclohexane Monoterpenes; Aged; pulegone; mikro RNA; Acetaminophen; Chemical and Drug Induced Liver Injury; MicroRNAs; lidé středního věku; monoterpeny s cyklohexanovým kruhem; senioři; mužské pohlaví; precision-cut liver slices; Middle Aged; Monoterpenes; Humans